VARIABLES AFFECTING EARNINGS MANAGEMENT (CASE STUDY OF COMPANIES IN THE FOOD AND BEVERAGE MANUFACTURING SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE) - Hendra Pratama; Dara Angreka Soufyan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to provide empirical evidence about the effect of bonus compensation, leverage, firm size and earning power on earnings management. This research was conducted at food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The method of selecting the sample in this study used a purposive sampling technique of 21 companies. The data analysis method used in this study uses multiple linear regression analysis. The results of this study indicate that the leverage and earning power variables partially affect earnings management. While the bonus compensation variables and company size partially have no effect on earnings management and bonus compensation variables, leverage,